Mycotic infections in rheumatology - B. S. Belov; G. M. Tarasova; D. V. Bukhanova (Современная ревматология, 2017)
Invasive mycoses are becoming a more relevant problem in modern rheumatology. There are difficulties in the lifetime diagnosis and treatment of mycoses in patients with rheumatic diseases. The significance of this issue increases considerably due to the active clinical introduction of biological agents. The paper provides general information on the clinical presentation, diagnosis, and therapy of the most common mycoses.